EFEK GLOBAL PADA PENURUNAN PEREKONOMIAN DI ASIA TIMUR DAN LEBIH KHUSUSNYA DAMPAKNYA TERHADAP PERTANIAN DAN INDUSTRI MAKANAN OLAHAN DI AMERIKA UTARA - SANTOSO CHANDRA (Media Bisnis, 2015)
Simulation of global economic growth to test the effects of the global economic slowdown in East Asia, and more particularly its impact on agriculture and processed food industry in North America that uses a dynamic model of GTAP and GTAP database version has been modified. The impact of the crisis in Asia against the length of world trade for agricultural production is indicated by a reduction in imports which will directly affect the economy. Overall agricultural products will also decrease. Decline in demand for agricultural products is followed by changes in the supply side. The crisis is setbacks that directly affect the economy of East Asia, not only revenue growth but also the development of the industry and its competitive ability in the long term.